Construction funding; where the money comes from - Halperin, Don A. (New York : Wiley, 1974)
The construction industry in the United States and other advanced nations continues to grow at a phenomenal rate. In the United States alone construction in the near future will exceed ninety billion dollars a year. With the population explosion and continued demand for new building of all kinds, the need will be for more professional practitioners. In the past, before science and technology seriously affected the concepts, approaches, methods, and financing of structures, most practitioners developed their know-how by direct experience in the field. Now that the construction industry has become more complex there is a clear need for a more professional approach to new tools for learning and practice. This series is intended to provide the construction practitioner with up-to-date guides which cover theory, design, and practice to help him approach his problems with more confidence. These books should be useful to all people working in construction: engineers, architects, specification experts, materials and equipment manufacturers, project superintendents, and all who contribute to the construction or engineering firm's success. Although these books will offer a fuller explanation of the practical problems which face the construction industry, they will also serve the professional educator and student.
Chapter 1. Sources of Money -- Chapter 2. Capitalization -- Chapter 3. Site Selection and Development -- Chapter 4. Preparing the Request for Funds -- Chapter 5. Draw Schedule -- Chapter 6. Cash Forecasting -- Chapter 7. Time Value of Money.
Includes index.
Keywords: BUDGET